PERANCANGAN DAN PEMBUATAN WEBSITE MARKETPLACE UNTUK PEMESANAN DAN PENJUALAN KOMODITAS PERTANIAN PADA KELOMPOK TANI (SENTANI SEJAHTERA) DOLOK SANGGUL - Mariana Tri Susanti; Fati Gratianus Nafiri Larosa; Indra Kelana Jaya (Majalah Ilmiah METHODA, 2018)
Today the marketplace plays an important role in providing ease of service for sellers and buyers, especially in the Sentani Sejahtera Farmers Group in Dolok Sanggul, North Sumatera. The existence of this marketplace website, buyers and sellers do not have to meet directly to carry out the process of trading agricultural commodities. The application of the marketplace system is to help farmers to inform and to sell their agricultural products to outside parties quickly through the concept of a website marketplace. The method used in this design is the Waterfall Method and Data Flow Diagram (DFD) as a system design tool. This application is also made using the Pre Hypertext Processors (PHP) programming language and uses MySQL as a database and other supporting software. With this application, it makes it easy for Sentani Sejahtera Dolok Sanggul farmer groups to sell their agricultural products easily and provide efficient and clear information to customers.